(untitled) (Dhaka University Journal of Biological Sciences, 2017)
A large body of research shows that individual’s perceived sense of connectedness with his or her community has a robust association with health, well‐being, and productivity. However, little is known about the factors that might influence oneʹs community connectedness (CC). Three hundred university students from three higher education institutes responded to a selfadministered questionnaire that included demographic, behavioural and psychological measures such as (i) perceived community connectedness, (ii) depression and (iii) Internet addiction. Results revealed that there was a significant positive association of CC with age, number of siblings and SES and a significant negative association with Internet addiction and depression. Multiple regression found age, socio‐economic status (SES), Internet addiction and level of depression were the significant factors influencing participants’ CC [F (7, 292) = 26.406, p < .001, Adj. R2 = 0.373]. Findings are discussed in the light of existing literature. Dhaka Univ. J. Biol. Sci. 26(2): 133-140, 2017 (July)